Education Achievements of Children of Employees Recipients of the Djarum Foundation Scholarship Primary Krapyak Kudus A Case Study - Robertus, Benny Hermawan; Su’ad, Su’ad; Murtono, Murtono (Asian Journal of Assessment in Teaching and Learning, 2022)
The aims of this study are to explain the educational achievements of the children of employees who are recipients of the Djarum Foundation scholarship at Djarum Company Primary Krapyak Kudus and to explain the obstacles in providing Djarum foundation scholarship assistance. Achievement relates to the assessment of how a product meets certain criteria, standards or references. In the world of education, this standard can be formulated through learning outcomes of scholastic subjects that can be measured quantitatively, and qualitative observations, especially in the fields of social knowledge. Meanwhile, Corporate Social Responsibility (CSR) is a concept which means that companies must have responsibilities towards employees, the community, and the surrounding environment in every operational activity. This research is a type of qualitative descriptive research. Sources of data in this study are primary data and secondary data. Data collection techniques using interviews, observation and documentation studies. The data analysis used in this research is interactive qualitative data analysis, while the validity test uses participation extension, observation persistence and triangulation. The results showed that the granting of the Djarum scholarship was able to improve the academic achievement of the children of Djarum employees who received the Djarum scholarship. The obstacles faced in the implementation of the Djarum Scholarship Plus Program were the problem of scheduling soft skills activities and accommodation, this was resolved by carrying out training activities in several waves. In addition, there are logistical problems for the transfer of goods needed in the implementation of soft skills training activities. This can also be handled properly over time with a trial and error process and become a consideration in implementing the program in the following year.